The Relationship Between Self-Efficacy, Self-Concept, and Family Support with Work Readiness in Generation Z - Mutiara Insani Anisykurli; Suryanto Suryanto; Dyan Evita Santi (Yayasan Adra Karima Hubbi, 2024)
Job readiness is a collection of abilities and skills from individuals to obtain a job that aligns with their capabilities. This study aims to determine the relationship between self-efficacy, self-concept, and family support, both partially and simultaneously, on Generation Z's work readiness. This research uses a quantitative approach. The population in this study consists of fresh graduates who live in Surabaya and belong to Generation Z. The sampling method used in this study is purposive sampling. The sampling method in this study was convenience sampling and included a total of 337 respondents. Data collection was conducted using a questionnaire in the form of a Google Form. Data analysis and testing techniques were processed with the help of the SPSS 26.0 for Windows program. The results showed that the self-efficacy variable partially had no significant relationship with work readiness, as evidenced by p = 0.284 > 0.05. The self-concept variable also did not show a significant relationship with work readiness, as evidenced by p = 0.458 > 0.05. The analysis of family support variables partially showed a significant relationship with work readiness, as evidenced by p = 0.028 < 0.05. Simultaneously, the results indicated a significant relationship, where F = 8.806 at p = 0.000 < 0.05, with the coefficient of determination (R2) being 7.3%. This study provides novelty in the work readiness variable, showing no relationship between the variables of self-efficacy and self-concept with work readiness.